The role of the genetic polymorphism of the gene - oncosupressor TP53 rs 17884159 in women with cervical intraepithelial neoplasia - Kamilova I.A (Central Asian Journal of Medical and Natural Science, 2021)
Analysis of the frequency of distribution of alleles and genotypes of polymorphism of the TP53 rs 17884159 gene depending on the severity of the disease at the time of the study showed negative associations, consisting in a significant increase in the prevalence of carriage of the heterozygous C/T genotype associated with the severity of CIN: carriage of the heterozygous C/T genotype increases the risk of pathology in LSIL 1.947 times; HSIL CIN ΙΙ - 3.957 times and HSIL CIN ΙΙΙ - 2.250 times. In our studies, the carriage of unfavorable C/T and T/T genotypes is associated with an increase in the severity of CIN